Implementasi Balanced Scorecard dalam Penyusunan Rencana Strategis di Rumah Sakit Cantia Tompasobaru - James Komaling; Jeini Ester Nelwan; Diana Vanda Daturada Doda (Universitas Sam Ratulangi, 2022)
Background: The vision and mission of the hospital must be achieved by every hospital. This requires planning as outlined in a document called a strategic plan. There are many approaches to strategy formulation, one of which is the Balanced Scorecard (BSC). BSC is an approach that is widely used today, including in hospitals. The purpose of this research was to formulate a strategic plan for Cantia Tompasobaru Hospital using the Balanced Scorecard method. Methode: This is a qualitative research with a case study design. This research was conducted in April-July 2022 at Cantia Tompasobaru Hospital. The number of informants, namely 10 informants consisting of key informants, namely level 2 of the hospital, consisted of 3 deputy directors, while the other informants, namely level 3 of the hospital, were the heads of each room and installation, totaling 7 people. The variables studied are the BSC perspective, namely the perspective of finance, customers, internal business processes, as well as learning and innovation. Data were obtained through interviews, focus group discussions, document review and field observations. The data obtained were analyzed by content analysis method. Result: The results showed that the customer perspective BSC strategy, there are 2 strategic goals, namely retaining old customers and attracting new customers. The strategic goals to retain existing customers have 4 strategies, namely meeting medical service expectations, meeting tariff and service quality expectations, meeting consumer service expectations and providing incentives or bonuses. The target strategy to attract new customers consists of 4 strategies, namely adding service products, providing price certainty, building relationships with doctors and increasing brand awareness. The internal business perspective BSC strategy has 2 strategic objectives, namely increasing key capabilities and improving business processes. The target strategy to increase the main capabilities has 3 strategies, namely improving clinical results, increasing value propositions, and improving customer service. The target strategy for improving business processes consists of 4 strategies, namely improving organizational structure, improving management systems, optimizing and improving processes and reducing loss/waste costs. The BSC strategy from a growth and development perspective has 2 strategic goals, namely increasing employee professionalism and improving the work environment. The target strategy for increasing employee professionalism has 2 strategies, namely increasing work direction and increasing knowledge and skills. The target strategy to improve the work environment consists of 2 strategies, namely maximizing the placement of staff/number of human resources and increasing work morale. The BSC hospital strategy from a financial perspective has 3 strategic objectives, namely increasing profit, increasing revenue and reducing costs. The target of the strategy to increase profits aims to enable hospitals to increase profits in order to support hospital development. The target strategy to increase revenue aims to increase the number of customers. The target strategy is to reduce costs with 4 strategies, namely increasing efficiency, main capabilities, business processes and productivity Conclusion: It can be concluded that the customer perspective BSC strategy, there are 2 strategic goals, namely retaining old customers and attracting new customers. The internal business perspective BSC strategy has 2 strategic objectives, namely increasing key capabilities and improving business processes. The BSC strategy from a growth and development perspective has 2 strategic goals, namely increasing employee professionalism and improving the work environment. The BSC hospital strategy from a financial perspective has 3 strategic objectives, namely increasing profit, increasing revenue and reducing costs.